An Assessment of Ground Water Quality in Selected Dug Wells in Vavuniya Urban Council Limit through Water Quality Index - Ravi, V.; Hareth, G.B.B.; Manobavan, M.; Sivakumar, S. (International Journal of Scientific and Engineering Research, 2016)
An assessment conducted in Vavuniya urban council limit from dug well water sample, the particular council consists nine Girama Niladhari Divisions. This study was assessed selected physio-chemical and biological parameters such as pH, electric conductivity, total suspended solids, total hardness, fluoride, nitrate, nitrate nitrogen, iron, free chlorine and total coli form in 90 dug well water. Totally six Girama Niladhari Division zone water quality index is below 50. This means the water quality is good. Other four Girama Niladhari Division zones water quality index are 92, 64, 63 and 58 respectively. This indicates the water quality is poor. The major reason for lowering water quality is the presence of fecal coli form, which is exceeded its allowable level.
Keywords: Ground Water